Towards training in specialized translation: facts and challenges - Perassi, María Laura; Ferreira Centeno, Ana (Íkala, Revista de Lenguaje y Cultura, 2015)
Within the context we are currently immersed in and within which we develop our activities, the need for linguistic and intercultural mediators trained and qualified in specialized translation practice has become pressing. As trainers of future translation professionals, we are quite aware of this reality, but at the same time, reaching out to these constantly evolving manifestations that need to —or should— be expressed in another language differently poses a permanent challenge to us. Despite advances in the field of translation training and the new theoretical approaches dealing with the subject of professional practice, to design an academic syllabus always involves new challenges. As teachers of specialized translation program in French at the School of Languages, National University of Córdoba, Argentina, we have to introduce our students to this particularly characteristic world. In this article, we intend to reflect upon certain key points regarding translators´ training in our environment —In which contexts, both geographical and working, will be future translators immersed? What knowledge level do students display in this introductory stage to specialized translation? How do we guarantee our students are comprehensively trained? Based on these questions, we will take a look at our educational reality and the challenges it poses, which will lead us to rethink our methodologies and the approaches related to specialized translation teaching.